Recycling and reuse of waste materials proceedings of the international symposium held at the University of Dundee, Scotland, UK on 9-11 September 2003 - Dhir, Ravindra K.; Newlands, Moray D.; Halliday, Judith E. (Thomas Telford, 2003)
A review of the latest advances in recycling and reuse of waste materials, along with discussion on how to encourage exploitation of waste that will benefit the environment and sustainable development.
Keywords: Refuse and refuse disposal -- Congresses.; Recycling (Waste, etc.) -- congresses.; elektronické knihy; electronic books